2011
DOI: 10.1515/bmc.2011.041
|View full text |Cite
|
Sign up to set email alerts
|

Senescence marker protein 30: functional and structural insights to its unknown physiological function

Abstract: Senescence marker protein 30 (SMP30) is a multifunctional protein involved in cellular Ca2+ homeostasis and the biosynthesis of ascorbate in non-primate mammals. The primary structure of the protein is highly conserved among vertebrates, suggesting the existence of a significant physiological function common to all mammals, including primates. Enzymatic activities of SMP30 include aldonolactone and organophosphate hydrolysis. Protective effects against apoptosis and oxidative stress have been reported. X-ray c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…26,31,32) The lungs of the SMP30-deficient mice in the current study did not show a significant increase of medial smooth muscle area in either normoxia or hypoxia. Although SMP30 has an anti-apoptosis effect, [33][34][35] further study is needed to clarify the survival of pulmonary arterial smooth muscle cells in hypoxia-exposed SMP30-deficient mice. There was no difference in the Fulton index between WT and SMP30 deficient mice after hypoxia in this study.…”
Section: Discussionmentioning
confidence: 99%
“…26,31,32) The lungs of the SMP30-deficient mice in the current study did not show a significant increase of medial smooth muscle area in either normoxia or hypoxia. Although SMP30 has an anti-apoptosis effect, [33][34][35] further study is needed to clarify the survival of pulmonary arterial smooth muscle cells in hypoxia-exposed SMP30-deficient mice. There was no difference in the Fulton index between WT and SMP30 deficient mice after hypoxia in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of p21 levels by Id1 augments the generation of EPCs in bone marrow . SMP30, a marker of senescence or aging, protects cells from apoptosis by inhibiting the caspase cascade and regulating Ca 2+ homeostasis . SMP30 has also been found to exert a protective effect against oxidative stress by enhancing ascorbate production and Ca 2+ modulation .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Matsumoto et al showed that cytosolic calcium regulates autophagy-related gene expression in autophagy-deficient mice [18] and that cytosolic Ca 2+ signaling is a critical regulator of cardiac myocyte function [13]. A pivotal anti-senescence marker, SMP30 (senescence marker protein 30), has been reported to regulate intracellular Ca 2+ homeostasis [19,20,21] and play a pathophysiological role in the tight regulation of Ca 2+ -related cell functions [22]. Recently, intracellular Ca 2+ signaling has been reported to have an important role in the regulation of autophagy [23]; however, its exact function remains controversial.…”
Section: Introductionmentioning
confidence: 99%